Shyness : how normal behavior became a sickness - Lane, Christopher, 1966- (Yale University Press, 2007)
Discusses the effects of expanding the Diagnostic and Statistical Manual of Mental Disorders (DSM)'s fourth edition on the psychiatric community, pharmaceutical companies, and the nation.